2015 Winter Simulation Conference (WSC) 2015
DOI: 10.1109/wsc.2015.7408169
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based model of maritime search operations: A validation using test-driven simulation modelling

Abstract: Mumtaz Karatas Department of Industrial EngineeringTurkish Naval Academy Tuzla, Istanbul, 34942, TURKEY Maritime search operations (and search operations in general) are one of the classic applications of Operational Research (OR). This paper presents a generic agent-based model for maritime search operations which can be used to analyse operations such as search and rescue and patrol. Agent-based simulation (ABS) is a relatively new addition to existing OR techniques. The key elements of an ABS model are agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…They perform DES model to EMS of Belo Horizonte, Brazil, with dynamic changes in the number of ambulances, bases and hospitals in six different scenarios. In their study, Onggo and Karatas (2015) and Onggo and Karatas (2016) use simulation to measure the performance of maritime search operations. Considering different maritime search problems, the authors develop a test-driven simulation modeling which utilizes analytic formulas to verify and validate their model.…”
Section: Related Workmentioning
confidence: 99%
“…They perform DES model to EMS of Belo Horizonte, Brazil, with dynamic changes in the number of ambulances, bases and hospitals in six different scenarios. In their study, Onggo and Karatas (2015) and Onggo and Karatas (2016) use simulation to measure the performance of maritime search operations. Considering different maritime search problems, the authors develop a test-driven simulation modeling which utilizes analytic formulas to verify and validate their model.…”
Section: Related Workmentioning
confidence: 99%
“…The work tends to focus on software architecture rather than analyzing collaboration from a market approach. Moreover, ABM is still a relatively new tool to operational research, compared to DES and SD (Onggo and Karatas 2015). The following subsections briefly discuss the features of ABM and the previous ABM research in a SCM context.…”
Section: Overview Of Agent-based Modelingmentioning
confidence: 99%
“…Another study [33] introduced a simulation process of sea-air search trends at sea using 3D GIS technology, which helps search commanders judge search trends, including search facility dynamics and the degree of area coverage. A case study using agent-based maritime search-operation simulation demonstrated a model verification and validation (V&V) technique called test-driven simulation modelling (TDSM) [34]. The optimal selection of vessels for participating in maritime search has been studied, and a corresponding model was established in [35]- [37].…”
Section: Introductionmentioning
confidence: 99%